1997
DOI: 10.1002/pen.11823
|View full text |Cite
|
Sign up to set email alerts
|

Study of mechanical damage in rubber‐toughened poly(methyl methacrylate) by single and multiple scattering of light

Abstract: A s glassy polymers are usually somewhat brittle, several blending techniques are used to toughen these materials and to increase their impact strength. The microstructures of toughened polymers are complicated, as are their mechanical damage mechanisms. Moreover, these materials are mostly opalescent or even opaque, which renders difficult any optical investigation of the damage process. The scale of the damage generally ranges from nanometers to several micrometers, thus requiring a large panel of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…The cavities, as shown by transmission electron microscopy, may comprise a unique small cavity in the center of a pure rubber particle, or a distribution of several smaller holes in the rubber wall of a composite particle. As discussed in our earlier work, 24 the light scatterers in these materials may be defined as follows.…”
Section: Light Scatterersmentioning
confidence: 99%
See 4 more Smart Citations
“…The cavities, as shown by transmission electron microscopy, may comprise a unique small cavity in the center of a pure rubber particle, or a distribution of several smaller holes in the rubber wall of a composite particle. As discussed in our earlier work, 24 the light scatterers in these materials may be defined as follows.…”
Section: Light Scatterersmentioning
confidence: 99%
“…There are two boundary cases where and v f may be determined from L if (i) the void content remains constant, and (ii) the number of damaged particles remains constant. These two situations were discussed in detail in our previous work 24 and the theoretical results were compared with experimental values in the two extreme cases of damage basically due to an increase in the void content of the particles, or to an increase in the number of damaged particles. It was shown that at low strain rates in RT-PMMA, the void content of the damaged particles remains constant during the elongation process.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations